Between-taxon matching of common and rare species richness patterns - Reddin, Carl James; Bothwell, John; Lennon, Jack (Global Ecology and Biogeography, 2015)
Keywords: Indicator; Intertidal ecology; Marine; Rarity; Spatial; Species richness; Surrogacy

Climate change and the latitudinal selectivity of ancient marine extinctions - Reddin, Carl James; Kocsis, Ádám; Kießling, Wolfgang (Paleobiology, 2018)
Geologically rapid climate change is anticipated to increase extinction risk nonuniformly across the Earth's surface. Tropical species may be more vulnerable than temperate species to current climate warming because of high tropical climate velocities and reduced seawater oxygen levels. To test whether rapid warming indeed preferentially increased the extinction risk of tropical fossil taxa, we combine a robust statistical assessment of latitudinal extinction selectivity (LES) with the dominant views on climate change occurring at ancient extinction crises. Using a global data set of marine fossil occurrences, we assess extinction rates for tropical and temperate genera, applying log ratios to assess effect size and Akaike weights for model support. Among the classical “big five” mass extinction episodes, the end-Permian mass extinction exhibits temperate preference of extinctions, whereas the Late Devonian and end-Triassic selectively hit tropical genera. Simple links between the inferred direction of climate change and LES are idiosyncratic, both during crisis and background intervals. More complex models, including sampling patterns and changes in the latitudinal distribution of continental shelf area, show tropical LES to be generally associated with raised tropical heat and temperate LES with global cold temperatures. With implications for the future, our paper demonstrates the consistency of high tropical temperatures, habitat loss, and the capacity of both to interact in generating geographic patterns in extinctions.<br
Keywords: marine invertebrates; Phanerozoic; Paleobiology Database; model selection; generalized least squares; habitat loss; temperature related stressors

Coastal upwelling drives intertidal assemblage structure and trophic ecology - Reddin, Carl James; Docmac, Felipe; Bothwell, John; Harrod, Chris; et al. (PLoS ONE, 2015)

Corrigendum to: Marine invertebrate migrations trace climate change over 450 million years (Global Ecology and Biogeography, (2018), 27, 6, (704-713), 10.1111/geb.12732) - Reddin, Carl James; Kocsis, Ádám; Kießling, Wolfgang (Global Ecology and Biogeography, 2020)
JUSTIFICATION The original results to Reddin, Kocsis, and Kiessling (2018) included an error in the code that intended to match geographical grid cells between neighbouring ages (“matched-cells” hereafter), via a nonsensical call to the subset() function. After correcting this coding mistake, we checked these results against those acquired with the matched-cells step omitted entirely. The results held only when the matched-cells step was omitted. This invalidated our original belief that matched-cells would help “homogenize geographical sampling coverage between consecutive ages”. The restriction to matched-cells results in a median loss of 23% of survivor species compared to without matched-cells (median = 118 survivor species per age to median = 153 without matched-cells). Additionally, we suspect that the two spatial corrections for sampling variation interfere with one another, that is, the use of (a) matched-cells and (b) subtraction of the sampling focus from the median genus range centre (to calculate the latitudinal deviation). We therefore reproduce the analyses without limiting data to matched-cells and present the updated results, including the five changed results figures, here. In summary, the changes to the results are minor and the scientific conclusions remain as originally stated. UPDATED VERSIONS OF KEY FIGURES All results hold following the omission of the matched-cells step, albeit with slightly weaker strength, with the central correlation decreasing from rho = 0.30 (p =.01) to rho = 0.24 (p =.034; Figure 1). Following the order of presentation in the original paper, the central correlation rises, as before, with (a) hemisphere-switching, but to rho = 0.39 (95% CIs = 0.19–0.56, optimum threshold = 126; Figure 2) instead of the original rho = 0.48 (95% CIs = 0.29–0.64, optimum threshold = 108 genera). The central correlation for the Southern Hemisphere remained insignificant (rho = 0.08, p =.6). If (b) the median latitudinal deviation was supplemented with the 0.2-quantile latitudinal deviation, when the Northern Hemisphere median occurrence palaeolatitude vacated the tropics, a substantial improvement to the central correlation is no longer observed (small increase to Rho = 0.26, 95% CIs = 0.04–0.46, rather than the original increase to rho = 0.40, 95% Cis = 0.19–0.57; see next paragraph). However, as in the original version, combining both hemisphere-switching and integrating the 0.2-quantile deviation (steps a and b), raised the central correlation to rho = 0.35 (95% CIs = 0.14–0.53), but did not improve upon using hemisphere-switching alone. (c) Weighting the correlation from the hemisphere-switching approach by the age inverse extinction rate resulted in the highest correlation strength, at rho = 0.41 (95% CIs = 0.2–0.58; Figure 3) instead of the original rho = 0.56 (95% Cis = 0.39–0.70). 1 Figure (Figure presented.) Latitudinal range shifts of Northern Hemisphere marine genera (black lines) are correlated with low latitude mean shallow seawater temperature (red lines, right-hand y axis). Temperature calculated from fossil shell oxygen isotopes following Veizer and Prokoph (2015). Grey shading around the thick black line shows bootstrapped 95% confidence intervals. For both variables, thick lines show a moving window of three consecutive bins. Thin lines show the unsmoothed bin-to-bin changes. This is the updated original Figure 2. Contributing genera median range centre = 23.6°. There is now no gap in the latitudinal deviation time series for the Northern Hemisphere. Latitudinal deviation mean is 0.60° (absolute mean = 1.93°). Geological periods are lightly shaded and abbreviated as O = Ordovician; S = Silurian; D = Devonian; C = Carboniferous; P = Permian; Tr = Triassic; J = Jurassic; K = Cretaceous; Pg = Palaeogene; N = Neogene 2 Figure (Figure presented.) The effect of changing a threshold minimum number of genera in “hemisphere switching” on the correlation of latitudinal deviation with climate. When the minimum threshold is reached, latitudinal deviations are sourced from the opposite hemisphere. Dotted lines show the correlation without any hemisphere switching, for northern and southern palaeo-hemispheres separately. Filled circles are p <.05. Serial autocorrelation in times series removed by generalized differencing. This is the updated original Figure 3. Optimum threshold of sampled genera = 126 3 Figure (Figure presented.) Time series of latitudinal range shifts of marine genera (black lines) improved by hemisphere switching alongside low latitude shallow seawater temperature (red lines, right-hand y axis). Details as in Figure 1. This is the updated original Figure 4. Contributing genera median range centre = 27.6°. Latitudinal deviation mean is 0.38° (absolute mean = 1.89°). All other descriptions as in Figure 1. O = Ordovician; S = Silurian; D = Devonian; C = Carboniferous; P = Permian; Tr = Triassic; J = Jurassic; K = Cretaceous; Pg = Palaeogene; N = Neogene The latitudinal deviation quantiles still show an increase in strength of relationship with climate from higher to lower quantiles (Figure 4, rho = −0.58, n = 9, p =.11; down from the original rho = –0.78, n = 9, p =.02), but the trend is only significant when the sampling focus vacated the tropics, approximately after the Carnian age (rho = −0.83, n = 9, p =.008; Figure 4; also see original Figure 1 at 230 myr). This is presumably because the highest and lowest quantiles are more affected by noise and only become useful when the median sampling focus is no longer opportunely positioned, that is, when the sampling centre vacates the tropics. Prior to the Norian age (Triassic), the correlation between latitudinal deviation and climate with hemisphere switching (i.e. step (a), above) is significant even without smoothing (rho = 0.34, 95% Cis = 0.04–0.58, ages n = 43). The slopes of warm and cool ages remain significantly different to each other (Z-statistic = −3.23, p =.0006; Figure 5). 4 Figure (Figure presented.) Correlation strength between shallow seawater temperature and genus latitudinal range shifts decreases from more equatorward (0.1-quantile, median palaeolatitude = 12.7°) to poleward genera (0.9-quantile, median palaeolatitude = 39.0°; quantile steps of 0.1). Solid symbols show Spearman's rho coefficients that 95% confidence intervals (dashed lines) overlap zero. Serial autocorrelation in times series removed by generalized differencing. This is the updated original Figure 5. The latitudinal means for the coloured lines are the mean sampling latitudes. The strongest correlation over all ages is with the 0.5-quantile (i.e. median, given in main text) but when the quantile time series are split, the post-Carnian 0.2-quantile has the strongest correlation (rho = 0.35, p =.036) 5 Figure (Figure presented.) Poleward migrations are more likely to be recorded by lower latitude sampling foci, (a) especially during warm ages (red line and points, age seawater temperature > Phanerozoic mean, slope = −0.20, p =.0005, n = 33). Each point represents one geological age. Blue line and points represent cool ages (age seawater temperature < Phanerozoic mean, slope = −0.02, n.s., n = 45). (b) Termplots of the independent effects of the predictor variables in a multiple regression including both temperature and sampling latitude as predictor variables for latitudinal deviations. Points are the partial residuals. This is the updated original Figure 6 The interpretation of these results is unchanged. Thanks are owed to Gwen S. Antell for noticing this error. The code was updated in the Dryad repository on January 10, 2020. The authors apologise for this error.
CRIS-Team Scopus Importer:2020-06-23

Increase in marine provinciality over the last 250 million years governed more by climate change than plate tectonics - Kocsis, Ádám; Reddin, Carl James; Scotese, Christopher R.; Valdes, Paul J.; Kießling, Wolfgang (Proceedings of the Royal Society of London, Series B: Biological Sciences, 2021)
Amidst long-term fluctuations of the abiotic environment, the degree to which life organizes into distinct biogeographic provinces (provinciality) can reveal the fundamental drivers of global biodiversity. Our understanding of present-day biogeography implies that changes in the distribution of continents across climatic zones have predictable effects on habitat distribution, dispersal barriers and the evolution of provinciality. To assess marine provinciality through the Phanerozoic, here we (a) simulate provinces based on palaeogeographic reconstructions and global climate models and (b) contrast them with empirically derived provinces that we define using network analysis of fossil occurrences. Simulated and empirical patterns match reasonably well and consistently suggest a greater than 15% increase in provinciality since the Mesozoic era. Although both factors played a role, the simulations imply that the effect of the latitudinal temperature gradient has been twice as important in determining marine provinciality as continental configuration.
CRIS-Team WoS Importer:2021-09-03

In situ decrease in rhodolith growth associated with Arctic climate change - Teichert, Sebastian; Reddin, Carl James; Wisshak, Max (Global Change Biology, 2024)
Abstract Rhodoliths built by crustose coralline algae (CCA) are ecosystem engineers of global importance. In the Arctic photic zone, their three-dimensional growth emulates the habitat complexity of coral reefs but with a far slower growth rate, growing at micrometers per year rather than millimeters. While climate change is known to exert various impacts on the CCA's calcite skeleton, including geochemical and structural alterations, field observations of net growth over decade-long timescales are lacking. Here, we use a temporally explicit model to show that rising ocean temperatures over nearly 100 years were associated with reduced rhodolith growth at different depths in the Arctic. Over the past 90 years, the median growth rate was 85 μm year−1 but each °C increase in summer seawater temperature decreased growth by a mean of 8.9 μm (95% confidence intervals = 1.32–16.60 μm °C−1, p < .05). The decrease was expressed for rhodolith occurrences in 11 and 27 m water depth but not at 46 m, also having the shortest time series (1991–2015). Although increasing temperatures can spur plant growth, we suggest anthropogenic climate change has either exceeded the population thermal optimum for these CCA, or synergistic effects of warming, ocean acidification, and/or increasing turbidity impair rhodolith growth. Rhodoliths built by calcitic CCA are important habitat providers worldwide, so decreased growth would lead to yet another facet of anthropogenic habitat loss.<br

Living to the range limit: Consumer isotopic variation increases with environmental stress - Reddin, Carl James; O'Connor, Nessa; Harrod, Chris (PeerJ, 2016)
Keywords: Diet; Intertidal; Isotopic niche; Littorinid; Physiological condition; Range limit; Stable isotopes; Stress gradient; Trophic niche width; Trophic variation

Marine biological responses to abrupt climate change in deep time - Kießling, Wolfgang; Reddin, Carl James; Dowding, Elizabeth; Dimitrijevic, Danijela; Raja, Nussaïbah Begum; Kocsis, Ádám (Paleobiology, 2024)
Ancient changes in the biosphere, from organismic traits to wholesale ecosystem changes, can be aligned with climate forcing across the Phanerozoic. Clear examples of abrupt climate warming causing biodiversity crises are primarily found between the Permian and Paleogene periods. During these times, catastrophic events occurred, resembling the extreme climate scenarios projected for the near future. The paleobiologic literature around these events generally supports the hypothesis that abrupt climate change was a dominant trigger of extinction and/or ecological crisis. When climate change and climate history are considered, virtually all post-Paleozoic global biotic events can be confidently attributed to climatic change, with abrupt warming (hyperthermal events) leaving the most consistent fingerprint. The combined stress of deoxygenation and warming are sufficient to explain marine extinction patterns across most hyperthermal events. Although ocean acidification may have contributed, the direct role of pH on the extinction toll of organisms is not consistently demonstrated. Future research can enhance the correspondence between the magnitudes of climatic changes and their biological impacts, even though observed rates of change cannot currently be compared across different timescales. Mimicking multi-scale approaches in modern ecology, paleontological approaches to climate impact research will benefit from specifically targeting scaling relationships.

Marine clade sensitivities to climate change conform across timescales - Reddin, Carl James; Nätscher, Paulina; Kocsis, Ádám; Pörtner, Hans Otto; Kießling, Wolfgang (Nature Climate Change, 2020)
Rapid climate change is postulated to cause marine extinctions, especially among climate-sensitive clades, traits and regions1–6. This premise is based on two hypotheses: (1) known individual physiological sensitivities scale up to macroecological selectivity patterns4,7,8 and (2) ancient hyperthermal events are appropriate models to anticipate ecological winners and losers of anthropogenic climate change9. Yet these hypotheses have largely escaped quantitative appraisal. Here we show that experimental responses of modern marine ectotherms to single and combined climate-related stressors (such as seawater warming, hypoxia and acidification) align with Phanerozoic fossil extinction regimes across clades and functional traits. Of climate-related stressors, the synergistic interaction between warming and hypoxia10, encumbering aerobic metabolism, has the greatest potency as a proximate driver of extinction. All else being equal8, this synergy particularly imperils modern warm-water organisms. Modern–fossil agreement is strongest at intermediate–high extinction intensities and hyperthermal events but may fail at extreme extinction events, perhaps due to rising prominences of, and interactions among, additional biotic and abiotic stressors. According to results from marine ectotherms, clade-based sensitivity of individuals to climate-related stressors scales up from subannual experiments and decadal range-shift response magnitudes11, to extinction selectivity patterns at ancient climate-related stressor events and the Phanerozoic durations of genera.
CRIS-Team Scopus Importer:2020-02-25

Marine invertebrate migrations trace climate change over 450 million years - Reddin, Carl James; Kocsis, Ádám; Kießling, Wolfgang (Global Ecology and Biogeography, 2018)
Aim Poleward migration is a clear response of marine organisms to current global warming but the generality and geographical uniformity of this response are unclear. Marine fossils are expected to record the range shift responses of taxa and ecosystems to past climate change. However, unequal sampling (natural and human) in time and space biases the fossil record, restricting previous studies of ancient migrations to individual taxa and events. We expect that temporal changes in the latitudinal distribution of surviving taxa will reveal range shifts to trace global climate change. Location Global. Time period Post‐Cambrian Phanerozoic aeon. Major taxa studied Well‐fossilized marine benthic invertebrates comprising stony corals, bivalves, gastropods, brachiopods, trilobites and calcifying sponges. Methods We track deviations in the latitudinal distribution of range centres of age boundary crossing taxa from the expected distribution, and compare responses across latitudes. We build deviation time series, spanning hundreds of million years, from fossil occurrences and test correlations with seawater temperature estimates derived from stable oxygen isotopes of fossils. Results Seawater temperature and latitudinal deviations from sampling are positively correlated over the post‐Cambrian Phanerozoic. Simulations suggest that sampling patterns are highly unlikely to drive this putative signal of range shifts. Systematically accounting for known sampling issues strengthens this correlation, so that climate is capable of explaining nearly a third of the variance in ancient latitudinal range shifts. The relationship is stronger in low latitude taxa than higher latitude taxa, and in warm ages than cool ages. Main conclusions Latitudinal range shifts occurred in concert with climate change throughout the post‐Cambrian Phanerozoic. Low latitude taxa show the clearest climate‐migration signal through time, corroborating predictions of their shift in a warming future.
Keywords: d18O; fossil; latitude; out of the tropics; Paleobiology Database; Phanerozoic; sampling bias; time series

Spatially Heterogeneous Responses of Planktonic Foraminiferal Assemblages Over 700,000 Years of Climate Change - Mathes, Gregor H; Reddin, Carl James; Kießling, Wolfgang; Antell, Gawain S; Saupe, Erin E; Steinbauer, Manuel J (Global Ecology and Biogeography, 2024)
Aim: To determine the degree to which assemblages of planktonic foraminifera track thermal conditions. Location: The world's oceans. Time Period: The last 700,000 years of glacial–interglacial cycles. Major Taxa Studied: Planktonic foraminifera. Methods: We investigate assemblage dynamics in planktonic foraminifera in response to temperature changes using a global dataset of Quaternary planktonic foraminifera, together with a coupled Atmosphere–Ocean General Circulation Model (AOGCM) at 8000-year resolution. We use ‘thermal deviance’ to assess assemblage responses to climate change, defined as the difference between the temperature at a given location and the bio-indicated temperature (i.e., the abundance-weighted average of estimated temperature optima for the species present). Results: Assemblages generally tracked annual mean temperature changes through compositional turnover, but thermal deviances are evident under certain conditions. The coldest-adapted species persisted in polar regions during warming but were not joined by additional immigrants, resulting in minimal assemblage turnover. The warmest-adapted species persisted in equatorial regions during cooling with similarly minimal assemblage change. Assemblages at mid-latitudes mostly tracked temperature cooling and warming. Main Conclusions: Planktonic foraminiferal assemblages were generally able to track or endure temperature changes: as climate warmed or cooled, bio-indicated temperature also became warmer or cooler, although to a variable degree. At polar sites under warming and at equatorial sites under cooling, the change in bio-indicated temperature was less than, or even opposite to, what would be expected from estimated environmental change. Nevertheless, all studied species persisted across the study interval, regardless of thermal deviance—a result that highlights the resilience and inertia of planktonic foraminifera on an assemblage level to the last 700,000 years of climate change.
CRIS-Team Scopus Importer:2024-08-30
Keywords: climate change ecology; conservation palaeobiology; glacial–interglacial cycles; plankton

Stable carbon and oxygen isotope geochemistry as provenance indicator for the picture stones on Gotland (Sweden) - Hänsel, Patrick; Oehrl, Sigmund; Ideström, Lena; Widerström, Per; Reddin, Carl James; Munnecke, Axel (GFF, 2023)
The picture stones from Gotland are one of the most famous and exceptional groups of monuments known from Swedish Prehistory. These carved memorial stones and their extraordinarily rich imagery are a unique source for the study of Late Iron and Viking Age culture and in particular Scandinavian pre-Christian religions. The Gotlandic picture stones are mainly made from the thickly layered limestones surrounding the reefs and bioherms of Gotland’s carbonate platform from the middle part of the Silurian (latest Llandovery to Ludlow, Telychian–Ludfordian). However, the exact origins of the picture stones’ raw materials on Gotland have remained undetermined. In this paper, we investigate the geological origin of the raw material by isotope geochemistry. Whereas the oxygen (δ18O) and strontium isotope ratio (87Sr/86Sr) were strongly altered by diagenesis the carbon isotope ratio (δ13C) is quite stable. Because the different geological units on Gotland show specific isotope signatures, the δ13C values from picture stones can be used to assign them to the respective geological unit, and thus to the source area of the raw material. This also allows for an estimation of transport distance minima between the raw material source area and the find place of each sampled picture stone. Most of the picture stones seem to be produced from local material with short transport distances, less than 10 km and only a few were transported at a far distance exceeding 10 km. In summary, the transport distance was dependent mostly on the local availability of picture-stone-suitable rocks.
CRIS-Team Scopus Importer:2023-12-01
Keywords: Carbon isotopes; Gotland; Iron Age; oxygen isotopes; picture stones; strontium isotopes; transport distances

The biogeographical imprint of mass extinctions - Kocsis, Ádám; Reddin, Carl James; Kießling, Wolfgang (Proceedings of the Royal Society of London, Series B: Biological Sciences, 2018)
Mass extinctions are defined by extinction rates significantly above background levels and have had substantial consequences for the evolution of life. Geographically selective extinctions, subsequent originations and species redistributions may have changed global biogeographical structure, but quantification of this change is lacking. In order to assess quantitatively the bio-geographical impact of mass extinctions, we outline time-traceable bioregions for benthic marine species across the Phanerozoic using a compositional network. Mass extinction events are visually recognizable in the geographical depiction of bioregions. The end-Permian extinction stands out with a severe reduction of provinciality. Time series of biogeographical turnover represent a novel aspect of the analysis of mass extinctions, confirming concentration of changes in the geographical distribution of benthic marine life.
Keywords: benthic; palaeobiology; mass extinctions; bioregions; networks

The effects of spatial scale and isoscape on consumer isotopic niche width - Reddin, Carl James; Bothwell, John; O'Connor, Nessa; Harrod, Chris (Functional Ecology, 2018)
1. The mean and variance of ecological variables are dependent on sampling attributes such as the coverage of environmental heterogeneity (sampling extent) and spatial scale. Trophic niche width is often approximated by bulk tissue stable isotopes of C and N, that is, the population isotopic niche. However, recent studies suggest that environmental heterogeneity (experienced by individuals) may be more important in defining the isotopic niche width than trophic variability. We hypothesised that isotopic niche width will increase monotonically with spatial scale, largely produced by environmental variation, for example, nutrient source.2. To refine this hypothesis, by describing the shapes of isotope scaling curves, we explored a previously published dataset describing three Chilean intertidal species representing different feeding guilds (grazing snails, suspension-feeding mussel). We tested these hypotheses on a new, larger dataset describing three functionally analogous intertidal species from Northern Ireland. We generated isotopic variance-area curves from a spatially explicit bootstrap and investigated the scale dependency of environment-isotope relationships, including wave exposure and sub-habitat heterogeneity.3. Spatial scale explained 50% of the variance in population isotopic niche widths (bivariate C-N ellipse area) by simple, nonlinear relationships. Finer scales (< 1-10 km lag) accounted for most variance. Scale dependence was strong for delta N-15 variance, of which > 40% was explained by modelling linear coefficients. A delta N-15 baseline gradient, or isoscape, dominated delta N-15 variance scaling patterns, from sheltered, terrestrially influenced embayments to exposed, pelagic-dominated coastline. Consumer delta C-13 variance had a weaker scale dependence, plateauing at mesoscales (> 20 km lag).4. We show that isotopic niche width is strongly dependent on sampling spatial extent, which controls the environmental heterogeneity experienced by individual consumers. Environmental heterogeneity must be accounted for before isotopic niche width can be considered to accurately represent trophic niche width. Studies conducted at different spatial scales are likely to identify different environmentisotope relationships.5. We recommend that spatial scale should be incorporated into sampling designs explicitly, easiest by maintaining a consistent lag distance or area within which populations are sampled. Identified isoscapes can be de-trended, where necessary.
Keywords: ellipse; limpets; marine; mussels; niche space; scale dependence; stable isotope ecology; trophic ecology

The r package divDyn for quantifying diversity dynamics using fossil sampling data - Kocsis, Ádám; Reddin, Carl James; Alroy, John; Kießling, Wolfgang (Methods in Ecology and Evolution, 2019)
Unbiased time series of diversity dynamics are vital for quantifying the grand history of life. Applications include identifying ancient mass extinctions and inferring both biotic and abiotic controls on diversification rates. We introduce divDyn, a new r package that facilitates the calculation of taxonomic richness, extinction and origination rates from time-binned fossil data. State-of-the-art counting protocols, and sampling standardization functions permit the reconstruction of biologically meaningful time series. Additional functions permit the partitioning of turnover rates by environmental affinity. Using divDyn, we display Phanerozoic-scale diversity dynamics of marine invertebrates. With the help of the core function and standard subsampling options, we revisit the hypothesis of declining taxonomic rates over time, mass extinctions and equilibrial diversity dynamics and assess their methodological dependency. Our results suggest that rates declined only over the early Phanerozoic, only three mass extinctions stand out clearly, and evidence of equilibrial dynamics is dependent on the used methods. The modular and fast implementation of published methods ensures traceability, reproducibility and comparability of future studies.
CRIS-Team Scopus Importer:2019-05-02
Keywords: diversity dynamics; extinction; fossil record; origination; Palaeobiology Database; subsampling

The stability of coastal benthic biogeography over the last 10 million years - Kocsis, Ádám; Reddin, Carl James; Kießling, Wolfgang (Global Ecology and Biogeography, 2018)
Aim We demarcate marine benthic global bioregions based on fossil and recent occurrence data. Our main goal is to compare past and present biogeography and to extract major abiotic drivers of biogeographical patterns. We specifically test the hypothesis that global biogeography has changed markedly after the climatic fluctuations of the past 10 Myr. Location Worldwide. Time period Recent; late Miocene?Pleistocene interval. Major taxa studied Benthic taxa with a rich fossil record: Bivalvia, Brachiopoda, Bryozoa, Gastropoda, Echinodermata, Decapoda and reef corals. Methods We use occurrence data from the Ocean Biogeographic Information System (OBIS) and the Paleobiology Database to construct compositional networks and outline objective marine bioregions of benthic marine invertebrates using the 'infomap' community detection algorithm. We assess the association of modern bioregions with a variety of environmental parameters by applying multivariate statistical analyses, such as principal components analysis, random forests and multiple logistic regressions. Results Recent first-order bioregions for the coastal ocean are, in general, consistent across all taxa. Seawater temperature surpasses nutrients, primary production and salinity as a predictor of modern bioregion distributions. Despite substantial climatic variations, late Cenozoic biogeographical patterns recorded in fossils are very similar to modern ones. Main conclusions Biogeographical boundaries within oceans are strongly controlled by temperature gradients, but open oceanic and continental barriers determine the global biogeographical structure. The joint structure of a landmass distribution, deep ocean basins and the latitudinal temperature gradient defines bioregionalization of the benthic marine habitat, which did not change substantially over the past 10 Myr.
Keywords: global; invertebrates; marine; networks; palaeobiogeography; recent biogeography; temperature

Trophic relationships between the large scyphomedusa Chrysaora plocamia and the parasitic amphipod Hyperia curticephala - Riascos, J; Docmac, Felipe; Reddin, Carl James; Harrod, Chris (Marine Biology, 2015)

Victims of ancient hyperthermal events herald the fates of marine clades and traits under global warming - Reddin, Carl James; Kocsis, Ádám; Aberhan, Martin; Kießling, Wolfgang (Global Change Biology, 2020)
Organismic groups vary non-randomly in their vulnerability to extinction. However, it is unclear whether the same groups are consistently vulnerable, regardless of the dominant extinction drivers, or whether certain drivers have their own distinctive and predictable victims. Given the challenges presented by anthropogenic global warming, we focus on changes in extinction selectivity trends during ancient hyperthermal events: geologically rapid episodes of global warming. Focusing on the fossil record of the last 300 million years, we identify clades and traits of marine ectotherms that were more prone to extinction under the onset of six hyperthermal events than during other times. Hyperthermals enhanced the vulnerability of marine fauna that host photosymbionts, particularly zooxanthellate corals, the reef environments they provide, and genera with actively burrowing or swimming adult life-stages. The extinction risk of larger sized fauna also increased relative to non-hyperthermal times, while genera with a poorly buffered internal physiology did not become more vulnerable on average during hyperthermals. Hyperthermal-vulnerable clades include rhynchonelliform brachiopods and bony fish, whereas resistant clades include cartilaginous fish, and ostreid and venerid bivalves. These extinction responses in the geological past mirror modern responses of these groups to warming, including range-shift magnitudes, population losses, and experimental performance under climate-related stressors. Accordingly, extinction mechanisms distinctive to rapid global warming may be indicated, including sensitivity to warming-induced seawater deoxygenation. In anticipation of modern warming-driven marine extinctions, the trends illustrated in the fossil record offer an expedient preview.
CRIS-Team Scopus Importer:2020-12-04
Keywords: climate change; extinction; fossil; metabolic activity; photosymbiont; selectivity